Aspectos químicos envolvidos nas interações de Citrus com fitopatógenos - Magnani, Rodrigo Facchini (2007)
This present thesis describes the development of analytical methodologies involving the HPLC-PDA-MS/MS coupling to verify the production of both polar and non-polar metabolites in orange trees produced by grafting Citrus sinensis onto Citrus limonea. By the use of such kind of method, it was possible to verify the production of both polymethoxy and glycosyl flavonoids. This method was then applied to plants with symptoms of two different diseases, Citrus Sudden Death (MSC) and Greening. Regarding this last disease, the methodologies were focused on detection of some analogous of benzoic acid like gentisic acid, orbicularin, salicylic acid and glycosyl salicylic acid. Another part of this work was focused on isolation and characterization of Alternariol (AOL) and Alternariol Monomethyl Ether (AME), mycotoxins produced in vitro by a phytopathogenic strain of Alternaria alternata and the molecule tenuazoic acid. These mycotoxins were also monitored using HPLC-DAD for 30 days in an attempt to find out a possible profile of their production. In addition, an analytical method involving HPLC-MS/MS was developed, validated and applied to quantify the amounts of AOL and AME in different parts of tangerines (i.e., on flavedo and on albedo tissues) with and without symptoms of Alternaria Brown Spot disease. The levels of such substances were about 17.4 ± 1.0 μg/kg of AOH and 3.5 ± 0.2 μg/kg of AME on flavedo. Some inhibition tests against Guinardia citricarpa, related to Black Spot disease, were also done with some isolated compounds. Five of these compounds showed to have 100% of inhibition in this test at concentration of 500 μg/mL: benzoic acid, 3,4,5-trimethoxibenzoic acid, 3,4-dimethoxibenzoic acid, and the glycosyl flavonoids naringin and rutin.